2010
DOI: 10.1515/mamm.2010.010
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the otterLutra lutrain an almost pristine Portuguese river: seasonality and analysis of fish prey through scale and vertebrae keys and length relationships

Abstract: The seasonal diet and size of fish prey of the otter Lutra lutra were studied in an almost pristine river of North Portugal (Paiva river) through the analysis of spraints collected during 1 year. To identify Iberian freshwater fish species (Salmo trutta, Micropterus salmoides, Lepomis gibbosus, Luciobarbus bocagei, Cyprinus carpio, Carassius auratus, Pseudochondrostoma polylepis, Achondrostoma arcasii, and Iberocypris alburnoides) consumed by the otter keys based on scales and vertebrae were first developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Interactions between seasonality and prey selection Seasonality in otter diet has been found in many studies (Carss et al 1990;Heggberget 1993;Clavero et al 2003;Copp and Roche 2003;Miranda et al 2008;Novais et al 2010). This study found an increased dependence on fish in winter which is a common trend and may be explained by one of three (nonmutually exclusive) hypotheses: (1) a scarcity of alternative, non-fish prey during winter months, (2) a scarcity or reduced availability of fish prey during summer months or (3) increased susceptibility of fish leading to opportunistic foraging by otters, in winter (see Clavero et al 2003 for discussion).…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 98%
See 1 more Smart Citation
“…Interactions between seasonality and prey selection Seasonality in otter diet has been found in many studies (Carss et al 1990;Heggberget 1993;Clavero et al 2003;Copp and Roche 2003;Miranda et al 2008;Novais et al 2010). This study found an increased dependence on fish in winter which is a common trend and may be explained by one of three (nonmutually exclusive) hypotheses: (1) a scarcity of alternative, non-fish prey during winter months, (2) a scarcity or reduced availability of fish prey during summer months or (3) increased susceptibility of fish leading to opportunistic foraging by otters, in winter (see Clavero et al 2003 for discussion).…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 98%
“…Since otters only consume an average biomass of 15-72 g per fish caught, they do not need to catch the larger classes of fish to meet their daily energy intakes (Ruiz-Olmo et al 2001). Of the cyprinids (minnows excluded), otters appeared to select the smallest (0-5 cm) individuals (see also Britton et al 2006), probably because they were the easiest to capture (Novais et al 2010), yet they appeared to seek out medium-sized (6-10 cm) perch and larger-sized (16-20 cm) pike, probably because otters are able to take these larger fish in shallow waters. Similar speciesspecific size selection was observed by Copp and Roche (2003) and Cote et al (2008, for North American otters).…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 99%
“…With the aim of assessing the variation of the otter diet throughout the course of one year and between stretches, we searched for otter faeces (referred to as ‘spraints’ hereafter) monthly, from December 2009 to November 2010. According to the methodology proposed by Ruiz‐Olmo and Delibes (), we selected four sampling sites (600‐m river length) per stretch (Figure ) and monthly collected five to six spraints per site whenever possible; we grouped those spraints per stretch and season (3 months), resulting in 60 spraints per group for diet analysis, a sample size higher than in other studies in Mediterranean rivers (Miranda et al ., ; Marques et al ., ; Novais et al ., ). We did not collect more spraints per site to avoid disturbing the natural sprainting behaviour of otters.…”
Section: Methodsmentioning
confidence: 97%
“…Clavero et al [81] noticed important seasonal effects in the consumption of amphibians by Eurasian otters, with the highest prevalence during the spawning periods of most amphibian species (late winter-spring). Novais et al [82] also noticed that amphibians are the most frequent food resource in spring, but fish are the most frequent food resource in autumn, winter, and summer. Parry et al [79] found that the palmate newt (Lissotriton helveticus) remains in Eurasian otter spraints in all months except for February and March.…”
Section: Consumption Of Salamanders In Higher Trophic Levelsmentioning
confidence: 99%